2022
DOI: 10.3389/fmed.2022.939098
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-free total intravenous anesthesia for thyroid and parathyroid surgery: Protocol for a randomized, double-blind, controlled trial

Abstract: BackgroundOpioid-free anesthesia (OFA) may improve postoperative outcomes by reducing opioid-related adverse effects. This study aims to evaluate the effects of OFA on postoperative nausea and vomiting (PONV), postoperative pain, and 30-day outcomes after thyroid and parathyroid surgery.MethodsThis two-center, randomized, double-blind, controlled trial will include 400 adult patients scheduled for thyroid and parathyroid surgery. Patients will be randomly assigned, 1:1 and stratified by sex and site, to an OFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Esketamine is a valid analgesic alternative to opioids to avoid opioid-related nausea and vomiting in the postoperative setting. 14 , 15 Thus, we demonstrated that Group OFA in the current study had a lower incidence of drowsiness, weakness, dry mouth, headache and dizziness, which in turn may have contributed to promoting patient physical discomfort and physical independence scores.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Esketamine is a valid analgesic alternative to opioids to avoid opioid-related nausea and vomiting in the postoperative setting. 14 , 15 Thus, we demonstrated that Group OFA in the current study had a lower incidence of drowsiness, weakness, dry mouth, headache and dizziness, which in turn may have contributed to promoting patient physical discomfort and physical independence scores.…”
Section: Discussionsupporting
confidence: 50%
“…Recent studies regarding enhanced recovery after surgery (ERAS) have shown that multimodal, opioid-free analgesia, could reduce stress mediators, improve perioperative management, and reduce functional and quality-of-life impairments. 15 Furthermore, the incidence of constipation, difficulty concentrating, itchiness and feeling confused did not show any difference between the groups. This may be attributed to the shorter duration Moreover, the incidence of hypotension was lower in Group OFA.…”
Section: Discussionmentioning
confidence: 79%
“…Hypotension is defined as either a 30% reduction in mean arterial pressure (MAP) from baseline or absolute MAP ≤65 mm Hg. Dual definitions for diagnosis of hypotension (either a relative reduction in MAP or an absolute threshold of MAP) have been used in many recent studies 20–25…”
Section: Methodsmentioning
confidence: 99%
“…Dual definitions for diagnosis of hypotension (either a relative reduction in MAP or an absolute threshold of MAP) have been used in many recent studies. [20][21][22][23][24][25]…”
Section: Study Outcomementioning
confidence: 99%
“…3,4 PONV has been associated with complications including pulmonary embolism, dehydration, disturbances in water and electrolyte balance, increased physical burden on patients, prolonged hospitalization, and higher medical costs. [5][6][7] Among the various factors influencing PONV, anesthesia-related factors such as inhaled anesthetics, intraoperative and postoperative opioid use, duration and type of anesthesia, and intraoperative infusion volume have been found to be particularly significant. 6,7 Multiple clinical studies have consistently identified opioid dose as the strongest independent risk factor for PONV in surgical patients.…”
Section: Introductionmentioning
confidence: 99%